THEORETICAL AND ORGANIZATIONAL BASES OF FORMATION OF STATE CONTRACT SYSTEM IN THE RUSSIAN FEDERATION - D. Shatsky (Вестник университета)
A theoretical and applied study of the foundations of the state contract system in Russia based on the Federal Law «On the contract system in the sphere of procurement of goods, works and services to ensure state and municipal needs» dated on 05.04.2013 № 44-FZ was conducted. The historical description of the formation and functioning of the contract system in the Russian economy is given. The main parameters that allow evaluating and analyzing the state of public procurement management system are highlighted. The comparative analysis of the essence of the us Federal contract system as a tool of nancial regulation of the economy with the Russian procurement system has been done.